A review on combustion behavior and mechanism of Ti alloys for advanced aero-engine - Shao, Lei; Li, Wensheng; Li, Dongyue; Xie, Guoliang; Zhang, Chunzhi; Zhang, Cheng; Huang, Jinfeng (Journal of alloys and compounds, 2023)
Ti alloys are widely used in aero-engines due to their excellent comprehensive performance. However, Ti alloys show ignition sensitivity, which is attributed to their poor heat conductivity, high oxidation heat and active chemical performance, especially in high-pressure compressors. This paper summarizes the combustion characteristics and mechanisms of Ti alloys. The thermodynamic conditions and physical models of Ti alloys combustion are established. The nature, characterization parameters and influencing factors of the combustion threshold are clarified. Several commonly used methods of the burn resistant property are introduced. Furthermore, the development tendency is prospected for improving Ti alloys safety services in aerospace.